2020
DOI: 10.1002/sd.2056
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment of energy sector development in China and European Union

Abstract: Energy efficiency, development of renewable energy resources, decarbonization, and energy security are the key energy policy priorities of the European Union and China. Based on data for the period 2005-2016, this study compares the status of energy sector development sustainability among 21 European Union Member States and China by applying the several Multi-Criteria Decision Making methods. Seven Member States including United Kingdom were excluded from the analysis due to Brexit or entering EU late like Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The energy and climate sustainability of countries and/or groups of countries constitutes a vast area of scientific research. Studies that look at the concept of sustainable development can be found in the available literature [23,[40][41][42][43][44][45][46][47][48][49][50].…”
Section: Research About Sustainable Energy and Climate Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy and climate sustainability of countries and/or groups of countries constitutes a vast area of scientific research. Studies that look at the concept of sustainable development can be found in the available literature [23,[40][41][42][43][44][45][46][47][48][49][50].…”
Section: Research About Sustainable Energy and Climate Developmentmentioning
confidence: 99%
“…Research on sustainable energy development and its level has concerned various countries [40][41][42][43][44][45][46][47] or groups of countries [23,[48][49][50]. However, the available literature lacks studies devoted to the assessment of the level of sustainable energy development in the EU-27 over the past 10 years.…”
Section: Research About Sustainable Energy and Climate Developmentmentioning
confidence: 99%
“…The quest of sustainability has also motivated the energy sector over the globe to adopt sustainable practices in production and delivery [22]. Therefore, global energy outlook is rapidly shifting towards renewable energy sources [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, although in the literature, some efforts used different methods to evaluate green growth efficiency and indicators. However, a few previous studies employed the Multiple Criteria Decision Making (MCDM) and fuzzy sets theory to assess green growth indicators (Su, Zhang, Zhang, & Streimikiene, 2020; Zeng, Hu, Balezentis, & Streimikiene, 2020; Zrobek, Kovalyshyn, Renigier‐Biłozor, Kovalyshyn, & Kovalyshyn, 2020). Particularly, there is no study in the current body of the literature regarding the application of fuzzy sets and MCDM methods in the field of green growth.…”
Section: Introductionmentioning
confidence: 99%